MANAJEMEN PENDIDIKAN ISLAM DALAM PENINGKATAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN MODERN DAARUS SUNNAH AL-ISLAMY WANGON - Sukanto, Sukanto (UNISAN JURNAL, 2023)
Discipline in education, not only applies to schoolchildren but also applies to various groups. One of them is the educational discipline of students. This study aims to find out how islamic education management in improving the discipline of students in modern islamic boarding schools daarus sunnah al-islamy wangon. This research uses qualitative descriptive research methods. Data collection techniques in the form of observations, interviews, and documentation. Data analysis includes data collection, data presentation, and drawing conclusions. The results of the study show that islamic education management planning in improving santri discipline is to formulate the objectives of student disciplinary education, make regulations for student discipline, and so on. Organizing Islamic Education Management in Improving Santri Discipline includes: appointing and making management structures according to their fields and expertise in handling students. Implementation of Islamic Education Management in Improving student discipline includes: providing direction regarding student disciplinary education; and so forth. Supervision of Islamic Education Management in Improving student discipline, namely: direct supervision, indirect supervision.